Penatalaksanaan Holistik Pada Anak Dengan Skabies Melalui Pendekatan Kedokteran Keluarga Di Wilayah Kerja Puskesmas Rawat Inap Way Kandis - Tika, Tiara Trias; Kayrus, Aila (Medula, 2024)
Scabies is a skin disease caused by infestation and sensitization of the parasite Sarcoptes scabiei var. hominis. The prevalence of scabies in the world reaches 300 million people each year. Scabies is often ignored because it is not life-threatening. However, this disease can become chronic and cause complications, and reduce the quality of life of sufferers. Therefore, proper holistic treatment is needed using a family medicine approach to achieve successful therapy. The purpose of this article is to apply the principle of a holistic and comprehensive family doctor approach in detecting internal and external risk factors and solving problems based on EBM (Evidence Based Medicine) which is family approach and patient centered. This study is a case report. The data obtained are primary data obtained through alloanamnesis, physical examination, and home visits and secondary data obtained from the patient's medical records. An. R aged 15 years came with complaints of itching since one month ago and there were small pin-sized bumps filled with clear fluid in the itchy area which were then scratched and burst. The patient was worried that the complaint would worsen and interfere with the patient's activities. Clinically, the patient was diagnosed with scabies (ICD-10 B.86; ICPC-2: S72). Furthermore, holistic management was carried out, namely intervention using poster media. In the evaluation, the results were obtained in the form of a better understanding of the disease and behavioral changes that had an impact on the success of therapy. After holistic and comprehensive management, the patient experienced an increase in knowledge about the disease by 37.5 points. Complaints of itching and pimples on the skin decreased and the patient had improved personal and environmental hygiene.